An Individual Development Plan for Pharmacy Students for Career Planning and Tracking Accreditation Standards - Gee, Deanna (Am J Pharm Educ, 2019)
Objective. To create and implement individual development plans (IDPs) to assist pharmacy students in career planning and tracking their achievement of ACPE Standards 2016, Standard 4, for Personal and Professional Development. Methods. First-year Doctor of Pharmacy students completed IDPs, which were subsequently reviewed to ensure they addressed components of the ACPE Standard 4 key elements: self-awareness, leadership, innovation and entrepreneurship, and professionalism. Faculty advisors were surveyed regarding the utility of IDPs. Descriptive statistics were used to evaluate the results. Results. Self-awareness (100%) and professionalism (100%) were the key elements most commonly documented by pharmacy students, followed by leadership (51%), and innovation and entrepreneurship (22%). Faculty advisors reported IDPs as beneficial for stimulating individualized career planning and tracking achievement of ACPE Standard 4. Conclusion. Most students enter pharmacy school recognizing the importance of self-awareness and professionalism, but require additional training to instill leadership and innovation/entrepreneurship skills. Individual development plans can be implemented in pharmacy education as a cornerstone of personal and professional development planning, as well as a means of tracking a school’s progress toward meeting accreditation standards.